Competências gerenciais do professor-gestor: um estudo com Coordenadores de Curso da graduação na Universidade Federal da Paraíba - Pessoa, Mariana Ferreira (2020)
The academic management of Federal Institutions of Higher Education is characterized by the professor acting as manager, in which he becomes responsible for the academic and managerial activities of a course, and often the professor-manager takes over the academic management without having developed the necessary competencies for the position. The main objective of this research is to understand the competences developed by professors as Course Coordinators of the Graduation Course at Campus I of the Federal University of Paraíba (UFPB). For this, it was a qualitative research of descriptive approach, in which a bibliographical, documental and field research was carried out. A semi-structured interview script was used with twenty course coordinators and the procedures adopted to treat and interpret the research data were carried out by means of content analysis. The competences elucidated by the undergraduate course coordinators were divided into six categories: Academic Competencies (Pedagogical); Management Competencies (Administrative); Institutional Competencies; Political Competencies; Technical/Technological Competencies; Socio-emotional Competencies. The findings indicate that the process of developing the competencies of course coordinators occurs through daily practice; by the influence of personal characteristics of those interviewed; through observation and exchange of experiences with colleagues who have been course coordinators and with the technicaladministrative staff who work in the secretariats of the coordinators; by reading the legislation of the UFPB; by the realization of courses offered by the university that help them in the use of electronic systems, among other processes. The results also demonstrate that academic management is complex and involves facing many challenges, in which the course coordinator seeks to develop competencies that enable it possible to fulfill his functions and managerial activities, since there are many duties of the professor-manager.